Effect of wood sawdust-derived biochar as a substrate component on leachate water quality - Lima, Daniele de Andrade Villarim; Stellato, Thamiris Brandino; Ulrich, Joao Cristiano; Silva, Danilo Lopes Costa e; Rezende, Fabiana Abreu de; Fungaro, Denise Alves (International Journal of Sustainable Energy and Environmental Research, 2025)
This study investigated the effect of biochar addition (14% w/w) on the concentration of nutrient ions present in the leachate from a commercial green roof substrate after contact with rainwater. Biochar sample was produced from wood sawdust at 450 ˚C via slow pyrolysis. The sawdust biochar was characterized by physico-chemical and hydraluic prosperties and techniques including X-ray fluorescence, Fourier transform infrared spectroscopy, X-ray diffraction, Raman and differential thermal analysis. The physical and chemical properties of green roof substrate were also determined. The biochar effectively reduced the total amount of nitrate, sulfate, and phosphate in the leachates relative to the substrate alone but did not show a significant effect on ammonium leaching. The results indicated that wood sawdust-biochar has appropriate characteristics to be applied as a component of substrates, as it has a porous structure and adsorption capacity, as well as adequate physical-hydric properties. In addition, the management of biochar obtained from agricultural waste can contribute to the achievement of the Sustainable Development Goals when used in sustainable alternatives such as green roofing.